The Relationship between Anthropometric Characteristics and Crawl and Breaststroke Performance in Adolescent Girl Swimmers - Shirin Yazdani; Nader Farahpour; Nafiseh Akbari (Islamic Azad University, Hamedan Branch, 2017)
Objective: The aim of this study was to investigate the relationship between anthropometric characteristics and crawl and breaststroke performance in adolescent girl swimmers with an emphasis on ratio of length and width of limbs to the height of subjects. Methods: Twenty adolescent female swimmers voluntarily participated in this study. Anthropometric variables, including height , length of thigh, leg, foot, arm, forearm and hand , arm span, widths of pelvic, shoulders, knees, wrists and ankles were measured using a tape measure and caliper. Then the ratio of length and width of limbs to the height of subjects was calculated. Pearson correlation test at a significance level of 0.05 was used for statistical analysis. Results: Significant relationship were found between crawl record and subjects’ height, thigh, arm and forearm lengths, arm span, shoulder width, the ratios of arm, palm and foot length to the height and ratio of arm span to height (p<0.05). Also, the relationship between breaststroke record and subjects’ height, arm and thigh lengths, arm span, shoulder and palm widths, the ratios of forearm and thigh lengths to the height, ratio of shoulder girdle width to height and ratio of shoulder girdle to pelvic width were all found to be significant (p<0.05). Conclusion: In addition to the effect of anthropometric characteristics such as height, arm, forearm, thigh lengths, arm span, palm and shoulder girdle widths on the performance of adolescent girl swimmers, the ratios of limb lengths and widths to the height and ratio of shoulder girdle to pelvic width were positively related with swimming record. Thus, it is recommended that to achieve better results in swimming talent, coaches consider the ratio of limbs to the height.